PENGARUH PENGGUNAAN METODE SQ3R (SURVEY, QUESTION, READ, RECITED, REVIEW) TERHADAP KEMAMPUAN MEMBACA INTENSIF SISWA KELAS 4 SDN TAMBAKROMO 1 GENENG - Gita Deva Tri Nuryani; Widya Trio Pangestu; Prima Rias Wana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The aim of the researchers in this study was to improve students' intensive reading skills at SD Negeri Tambakromo 1 Geneng in Indonesian subjects. This study uses a quantitative method (experimental) with a one group pretest-posttest design. This study uses interviews and tests. The result of the interview is that the students' reading ability is good but there are 8 students who have low reading ability. The method used by the teacher is a lecture in every lesson. The learning outcomes of students who reached the KKM were only 15 students in intensive reading learning. From the research results tcount> t table = 8.419> 1756 SQ3R method has a significant effect on intensive reading ability in 4th grade students of SDN Tambakromo 1. Because if t Count > tTable then it means, H0 is rejected and Ha is accepted. Likewise with the results of the significance of Sig.(2-tailed) is 0.015, the result is less than 0.05 then H0 is rejected and Ha is accepted. SQ3R method has a significant effect on intensive reading ability in grade 4 students at SDN Tambakromo 1.